2018
DOI: 10.1021/acs.est.8b00300
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Decreases Dimethylarsinic Acid Concentration in Rice Grain and Mitigates Straighthead Disorder

Abstract: While root Si transporters play a role in the uptake of arsenite and organic As species dimethylarsinic acid (DMA) and monomethylarsonic acid (MMA) in rice ( Oryza sativa L.), the impact of Si addition on the accumulation of DMA and MMA in reproductive tissues has not been directly evaluated, particularly in isolation from inorganic As species. Furthermore, DMA and MMA are suspected causal agents of straighthead disorder. We performed a hydroponic study to disentangle the impact of Si on accumulation of DMA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…Recent research, however, has shown that an increase in DMA uptake occurs on expression of the OsNIP2:1 aquaporin channel (Zhao et al 2013). As well, in hydroponic experiments, an increase in Si media concentrations decreased DMA concentrations in rice plants (Limmer et al 2018). Thus, DMA uptake mechanisms and the role of Si in these mechanisms require further investigation.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent research, however, has shown that an increase in DMA uptake occurs on expression of the OsNIP2:1 aquaporin channel (Zhao et al 2013). As well, in hydroponic experiments, an increase in Si media concentrations decreased DMA concentrations in rice plants (Limmer et al 2018). Thus, DMA uptake mechanisms and the role of Si in these mechanisms require further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…Unlike for As III , Si transporters are unlikely to be responsible for the uptake of DMA, although Li et al (2009) have shown that the root silicic acid transporter OsNIP2:1 may play a role in DMA uptake. As well, Si has been shown to substantially decrease the uptake of DMA by some rice cultivars in hydroponic experiments (Limmer et al 2018). The role of Si transporters in DMA uptake remains unclear.…”
Section: Environmental Chemistry Processes Underlying As Uptake and Amentioning
confidence: 99%
See 1 more Smart Citation
“…First, regardless of whether a Si amendment increases porewater As relative to Control (Figure 1A), its ability to also provide sufficient Si to porewater after competitive desorption of arsenite in bulk soil ( Figure 1B) allows for Si to compete with As for root-uptake via the highly-efficient Si/As root transport pathway [57,58] in rice. Second, higher exogenous Si leads to decreased gene expression of Si root transporters [59][60][61], thus restricting the potential pathways (i.e., Si/As root transporters) for As uptake. Third, higher exogenous Si promotes ferrihydrite-rich plaque (Figure 3 and ref.…”
Section: Discussionmentioning
confidence: 99%
“…Regression models for arsenic in rice plant (Y) and soil property (variable) in soils fertilized with two chicken manures without or bearing roxarsone metabolites (CM and ROXCM), respectively. It is noticeable that the increased DMA in brown rice caused by ROXCM application might not pose serious arsenic health impact to human due to its low toxicity to organisms (Zhao et al, 2010), however, it might lead to "straighthead" symptom, a physical disorder linked with arsenic (DMA in particular) in rice plant (Agrama and Yan, 2009;Limmer et al, 2018;Rahman et al, 2008;Yan et al, 2005).…”
Section: Tablementioning
confidence: 99%